Analisis Fasilitas Cuci Tangan Pasar Tradisional di Kecamatan Klungkung pada Masa Pandemi COVID-19 - A.A Gde Wahyu Sparsayoga; Made Rismawan; Putu Ayu Ratna Darmayanti (Jurnal Kesehatan Medika Udayana, 2023)
Background: Hand washing facilities are one of the facilities that must be provided in public facilities such as markets to prevent the spread of the COVID-19 virus. The use of public hand hygiene facilities is required before passing through entrances and locations that are easily accessible in crowded areas so that people and traders can easily wash their hands during the COVID-19 pandemic. Purpose:To find out the description of traditional market hand washing facilities in Klungkung District during the COVID-19 pandemic. Method: The research design used in this study is a descriptive study with a cross-sectional approach which was carried out on April 30 - May 1, 2021. The population in this study were all hand washing facilities at traditional markets in Klungkung District. The sampling technique used is non-probability sampling. Data collection tools used in the form of observation sheets. Data analysis using univariate analysis. Results:The results showed that most of the traditional market hand washing facilities were in sufficient condition as many as 4 markets (57.1%) and were in good condition as many as 3 schools (42.9%). Conclusion: It is recommended to all market managers to continue to pay attention to the availability of components of hand washing facilities complete with clean conditions to prevent the chain of disease transmission during the COVID-19 pandemic.